A novel non-invasive sweat lactate biosensor and its application in human exercise monitoring - Xin, Haolin; Wei, Zilin; Qin, Yingkai; Wei, Aili; Chen, Kang; Xu, Longfei; Li, Bin; Wang, Kun; Wang, Tianhui (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionLactate is a key biomarker for clinical diagnostics and athletic performance monitoring. Conventional blood-based assays are invasive and not ideal for real-time applications. Sweat, as a non-invasive alternative, offers significant advantages for dynamic lactate tracking.MethodsWe developed a highly sensitive fluorescence resonance energy transfer (FRET)-based aptasensor for lactate detection in sweat. The sensing platform utilizes aptamer-functionalized core–shell upconversion nanoparticles (APT-CS-UCNPs) as energy donors and Fe3O4-decorated molybdenum disulfide (MoS2) nanosheets as quenchers. In the absence of lactate, efficient FRET occurs due to the close proximity (<10 nm) between the donor and acceptor, quenching fluorescence at 545 nm. Lactate binding induces conformational changes in the aptamer, increasing donor–acceptor distance and restoring fluorescence intensity.ResultsThe aptasensor exhibited a broad linear detection range (0–30 mM, R2 = 0.9981) and an ultralow detection limit (0.07785 mM), outperforming most reported electrochemical sensors. In spiked sweat samples, recovery rates ranged from 98.45% to 104.28%, with negligible cross-reactivity to common interferents. Comparative analysis with commercial kits and previously published methods confirmed superior sensitivity and ease of operation.DiscussionThis FRET-based aptasensor enables accurate, rapid, and non-invasive lactate quantification using standard laboratory instrumentation. Its successful application in real human sweat samples highlights strong potential for both clinical diagnostics and athletic performance monitoring.